Kadar Serum Glutamic Oxaloacetic Transaminase (SGOT) pada Tikus Wistar (Rattus norvegicus) Jantan yang Dipapar Stresor Rasa Sakit Electrical Foot Shock selama 28 Hari (The Level of Serum Glutamic Oxaloacetic Transaminase (SGOT) in Male Wistar Rat (Ratt - Nur Lely Yaumil Qodriyati; Erna Sulistyani; Budi Yuwono (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Stress is a natural reaction that allows the human compelled to face the difficulties. Stimuli that causes stress can be physical and psychological. Physical stressors can occur continuously or sustained, which causes pathological processes in the body. This pathological process may be occur in liver and heart. One of parameter to assess characteristics of tissue can use Serum Glutamic Oxaloacetic transaminase (SGOT). The aim of this study was to prove differences level of SGOT in male Wistar rats (Rattus norvegicus) that exposed and control group were not exposed by pain stressor electrical foot shock for 28 days. Blood sampling was carried out on day 28 in intracardiac then tested the levels of SGOT. Statistical analysis showed that there was no significant change (p≤0,05) between control and treatment group. Liver damage from stressors may be not cause necrosis of liver cells. SGOT was not a single biomarker that was specific and sensitive for the diagnosis of liver disease because SGOT was also found in the heart. Keywords: electrical foot shock, SGOT, stress